Microcontroller Based Water Level Indicator And Controller System - Saha, Dwaipayan; Mukherjee, Indrani; Roy, Jesmin; Chatterjee, Sumanta (International Journal of Computer Sciences and Engineering, 2019)
The Water level indicator is a modification of an alarm system that is used in water tanks (not mandatory, can be used in any liquid container) to measure the water level and to indicate respectively. This article is mainly focussed on how can we save water from wastage as the amount of water is decreasing day by day due to various issues. Here we are using an Arduino UNO and an ultrasonic sensor to sense the water level so that we can aware of the people. Buzzers are used for buzzing purpose and an LCD is used for the display. Here the Arduino and the ultrasonic sensor make this model quite simple and easily can be modulated. This model is full of advanced technologies and its quite a user- friendly.